Frequency of Hypomagnesaemia in Severe Acute Malnutrition, Aged 6–59 Months - Sara Maqsood, Shazia Rizwan, Rabeya Rehman, Sobia Qamar, Sobia Shahalam, Saima Batool (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: to determine the frequency of hypomagnesaemia in severe acute malnutrition, aged 6 – 59 months. Methodology: Patients admitted in Pediatric Medical Unit of Children Hospital, Lahore fulfilling the inclusion criteria were enrolled in the study. Their MUAC along with weight for height/length was taken and also examined for bilateral pitting edema. Venous sample was taken for serum magnesium level and studied in labs of CHL. Hypomagnesaemia was labeled as per operational definition. Treatment given in form of magnesium sulfate after confirming hypomagnesaemia. Results: Of 200 cases, 58%(n=116) were between 6-36 months of age whereas 42%(n=84) were between 37-59 months. mean +sd was calculated as 34.9+11.36 months. 50.5%(n=101) were male while 49.5%(n=99) were female, mean magnesium level was calculated as 1.94+0.30 mg/dL. Frequency of hypomagnesemia in severe acute malnutrition, aged 6 – 59 months was recorded in 31.5%(n=63) of the cases. Conclusion: frequency of hypomagnesemia is significantly higher in cases with malnutrition, however, a larger study is required to record the rate of this morbidity in our region. Keywords: Malnutrition, hypomagnesemia, 6-59 months of age